Internacionalização tardia das empresas brasileiras e políticas públicas para incentivá-las - Panzini, Fabrizio Sardelli (2012)
Leaded, for a long time, by large transnational corporations from developed countries, the productive internationalization activity is gaining new players from developing countries. Firms from Brazil are part of that list, but the Asian corporations are the most prominent. Negative comprehension about capital outflows are criticized by recent studies that associate the internationalization process as being economic and socially beneficial to home countries as well as competitive gains for the private agents. That is the reason behind public policies to incentive this activity were and are being adopted with higher intensity by countries of late internationalization. Government support to enterprises internationalization, according to UNCTAD s categories, might occur by removing capital controls, financing, international agreements and fiscal incentives. From this scenario, the present study investigated the mechanisms applied by late comers that succeeded, in order to contribute with elements to define a governmental strategy to promote foreign investments from Brazilian enterprises